Changes in the fish community of the upper Tiber River after construction of a hydro-dam - Elisabetta Franchi (Journal of Limnology, 2014)
The aim of this study was to assess whether the composition of the fish community in the upper Tiber River Basin changed after the construction of the Montedoglio Reservoir by comparing the composition of the fish assemblages before and after the creation of this structure. Data collected in 2010 from three different sampling sites (one above and two downstream from the dam) were compared with those recorded during previous studies (conducted in 1992) to reveal the change in fish community. In each sampling site, a census of the fish community was conducted, the estimated number of fish of each species was calculated and fish condition was assessed by relative weight. The structure of the communities downstream from Montedoglio Reservoir changed radically after the construction of the barrier, while the fish community upstream from the barrier appeared unaffected by the dam. The release of hypolimnetic cold water from the reservoir, over time, has caused a progressive decreasing of water temperature of the Tiber River. Montedoglio Reservoir and the release of hypolimnetic water had a marked impact on the fish community of the Tiber River because it interrupted the typical longitudinal zonation of the species in the river. In addition, without effective management, this reservoir can pose an increased threat to the native fish species, since it is a source of diffusion of various exotic species.